Vitexin alleviates ox-LDL-mediated endothelial injury by inducing autophagy via AMPK signaling activation. (May 2017) - Zhang, Shaoli; Guo, Changlei; Chen, Zhigang; Zhang, Peiyong; Li, Jianhua; Li, Yan
Highlights: Vitexin promotes cell viability and suppresses apoptosis in ox-LDL-treated HUVECs. Vitexin inhibits the expression of ox-LDL-induced inflammatory factors and adhesion molecules. Vitexin suppresses ox-LDL-induced oxidative stress in HUVECs. Vitexin attenuates ox-LDL-induced endothelial injury by inducing autophagy. Vitexin protects HUVECs against ox-LDL-induced injury by activating AMPK signaling. Abstract: Endothelial cell injury plays a crucial role in the development and pathogenesis of cardiovascular disease. Vitexin is a natural flavonoid characterized by anti-oxidative and anti-inflammatory properties. The purpose of this study was to investigate the effects of vitexin on ox-LDL-induced endothelial dysfunction and to explore the underlying molecular mechanisms. In the present study, vitexin was found to play a protective role against ox-LDL-induced endothelial injury. Vitexin significantly promoted cell viability and inhibited apoptosis in ox-LDL-treated HUVECs. The up-regulation of cleaved Caspase-3, cleaved Caspase-9 and Bax induced by ox-LDL were inhibited by treatment with vitexin; meanwhile, the down-regulation of Bcl-2 was suppressed by vitexin. Pretreatment with vitexin was found to inhibit the ox-LDL-induced overexpression of IL-1β, IL-6, TNF-α, E-selectin, ICAM1 and VCAM1. Moreover, vitexin reduced ox-LDL-induced oxidative stress by inhibiting the production of ROS and MDA, and by promoting the expression of SOD. Furthermore, we had shown that vitexin protected against the ox-LDL induced cell injury by activating autophagy. The protective effects of vitexin in ox-LDL-treated HUVECs were all reversed following treatment with the autophagy inhibitor 3-MA. In addition, we found that vitexin increased the expression of p -AMPK and decreased the expression of p -mTOR. The combination of the AMPK inhibitor Compound C plus vitexin significantly reversed the effects of vitexin in ox-LDL-treated HUVECs, such as the inhibition of autophagy, reduction in cell viability, increase in apoptosis and ROS production. In conclusion, these data suggest that vitexin ameliorates ox-LDL-mediated endothelial injury by inducing autophagy via AMPK signaling.